2015
DOI: 10.18052/www.scipress.com/ilshs.58.1
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Quotient and Ethical Values towards Organizational Sustainability

Abstract: ABSTRACT. During the last decade, many organizations were collapsed and had damage their organizational sustainability reason being severe ethical crisis. One of the main reasons affecting organizational sustainability is unethical behavior in the organization. Therefore, the question arises, how this grave issue of unethical behavior of employees can be solved? This paper seeks to assess if spiritual quotient (Here after SQ) is a solution to the unethical behavior of employees and how this SQ along with ethic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Spiritual employees who work for organisations are assumed to be more honest and ethical (Akhtar et al , 2015). Scholars have linked employee behaviour with SQ.…”
Section: Employee Behaviour In the Organisationmentioning
confidence: 99%
“…Spiritual employees who work for organisations are assumed to be more honest and ethical (Akhtar et al , 2015). Scholars have linked employee behaviour with SQ.…”
Section: Employee Behaviour In the Organisationmentioning
confidence: 99%
“…Studies reveal that spiritual intelligence has multi-functional benefits. Akhtar et al, (2015) found that it enables employees to have access to deep meaning, abide to fundamental values in everyday routine, and think out of the box in order to accomplish their desired goals. Vaughan (2002) says it can facilitate task performance because employees are able to use spiritual resources to maneuver work-related challenges.…”
Section: Relationship Between Spiritual Intelligence and Organizationmentioning
confidence: 99%
“…Given this backdrop, literature indicates that spiritual intelligence can be potentially beneficial to a number of organizational variables (Antunes, Silva, & Oliveira, 2017;Mahmood, Arshad, Ahmed, Akhtar, & Khan, 2018). Studies on spiritual intelligence reported its positive relationship with organizational outcomes, such as organizational learning (Pluta & Rudawska, 2016); organizational sustainability (Akhtar, Arshad, Mahmood, & Ahmed, 2015); organizational citizenship behaviour (Hunsaker, 2016), job satisfaction (Roof, Bocarnea, & Winston, 2017), leadership performance (Ramachandaran, Krauss, Hamzah, & Idris, 2017), business management (Fontaine, 2018), and leadership performance (Osman-Gani & Hassan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Henderson, 2018) about social mission in social entrepreneurship is considered as business acts aiming to help resolving social problems within a community. In fact, the most applicable and significant mission in running their social business for these local social workers is spiritual mission (Akhtar, 2015). However,…”
Section: 3a Social Entrepreneur Who Does Not Run Any Social Businessmentioning
confidence: 99%